2022
DOI: 10.1177/00368504221144439
|View full text |Cite
|
Sign up to set email alerts
|

Social networking smartphone applications and emotional health among college students: The moderating role of social support

Abstract: Young people are increasingly using social networking site (SNS) smartphone applications (apps), necessitating research on the effects of such use on the users’ emotional health. The present study recruited 360 college students across mainland China and recorded their smartphone usage for one week using an automatic tracking app. Surveys assessing social support perception and emotional health were subsequently conducted. The study examined the relationship between SNS smartphone app usage (frequency and durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…Attitudes refer to an individual's positive or negative evaluation of a specific behaviour , whereas subjective norms refer to an individual's perception of social pressure or influence from significant others to perform a particular behaviour (Ajzen, 1991;Ling et al, 2023;. PBC refers to an individual's belief in their ability to successfully perform a behaviour (Ajzen, 1991;Ling et al, 2023;. As mentioned earlier, several studies have used TPB to examine consumers' this as behaviour in different contexts, and green consumption is no exception.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
See 4 more Smart Citations
“…Attitudes refer to an individual's positive or negative evaluation of a specific behaviour , whereas subjective norms refer to an individual's perception of social pressure or influence from significant others to perform a particular behaviour (Ajzen, 1991;Ling et al, 2023;. PBC refers to an individual's belief in their ability to successfully perform a behaviour (Ajzen, 1991;Ling et al, 2023;. As mentioned earlier, several studies have used TPB to examine consumers' this as behaviour in different contexts, and green consumption is no exception.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
“…While this remains limited in Ghana, understanding the use of TPB in understanding GCB remain elusive. The results of attitude as key concept in TPB model has been inconclusive, with some studies (Casal o and Escario, 2018;Sharma and Foropon, 2019;Sreen et al, 2018;Yadav and Pathak, 2016;Zheng et al, 2020;Zhuang et al, 2021) finding a significant positive effect of attitude on GCB, whereas others (Ling et al, 2023;Moser, 2015;Naz et al, 2020;Temizkan, 2022) found a weak relationship. We posit that the inconclusive outcomes of prior research on consumer attitudes towards green consumption can be attributed to the manner in which attitudes are conceptualised.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations